Pengembangan Kartu Kuartet Pelajaran Seni Budaya dengan Pendekatan Emosi bagi Siswa Tunagrahita - Yasin, Mohammad; Saleh, Hasdiana; Mohamad, Isnawati (Ideas Publishing, 2024)
The development of educational media for seventh-grade students with intellectual disabilities at SLBN Kota Gorontalo requires an effective approach. This study aims to develop quartet card media with an emotional approach using the ADDIE model. Data were collected through observation, interviews, documentation, questionnaires, and literature studies, and then analyzed qualitatively and quantitatively. The results show that the quartet cards are valid and feasible to use (100% material validation, 98% media validation) and highly effective (99.2% effectiveness). The quartet cards enhance student interaction and understanding, making learning more enjoyable and interactive.